2011
DOI: 10.1111/j.1749-771x.2011.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing southern Taiwanese men's acceptance of prostate-specific antigen screening

Abstract: Prostate‐specific antigen (PSA) testing is a common screening among adult men for early awareness of prostate cancer. Although prostate cancer is the seventh most common cause of death from cancer in males in Taiwan in 2008, this testing is still unpopular in Taiwanese society. The purpose of this study was to explore the prevalence of acceptance of PSA testing and related factors in Taiwanese males. A cross‐sectional study was conducted. The sample population was recruited from two counties in southern Taiwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that Japanese men were inadequately aware of prostate cancer and of the means available for its early detection, with only 8% of men having heard of PSA testing [24]. Additionally, previous studies have found a low acceptance of PSA testing among Taiwanese men [33] and that 58% of Korean men were not willing to take screenings because of the belief that they were healthy [26].…”
Section: There Is a Gap In Hcp-patient Communicationmentioning
confidence: 99%
“…Studies have shown that Japanese men were inadequately aware of prostate cancer and of the means available for its early detection, with only 8% of men having heard of PSA testing [24]. Additionally, previous studies have found a low acceptance of PSA testing among Taiwanese men [33] and that 58% of Korean men were not willing to take screenings because of the belief that they were healthy [26].…”
Section: There Is a Gap In Hcp-patient Communicationmentioning
confidence: 99%